Examen especial al proceso de control interno de la cuenta inventarios de la empresa Exfru S.A. en junio del 2019. - Guartizaca Durán, Jenny Paola (My University, 2021)
The execution of a Special Audit Examination entails a great deal of responsibility and commitment on the part of the audit team and an infallible commitment on the part of the company throughout its organisational structure. The audit is indispensable, as it allows us to prevent or face problems and possible significant risk patterns; its stages are very explicit and lead us to know from the real problems of the company to its possible solutions. Here we use the descriptive-explanatory methodology for the efficient and truthful investigation that is supported by the scientific articles presented. This case study is aimed at the exhaustive review and analysis of the internal control process over the merchandise inventories carried out by the company EXFRU S.A. in the period of June 2019. Based on techniques and procedures applied during the audit process, it has been possible to obtain relevant and decisive information for the company, such as the verification of the fatal breach of existing policies, irresponsibility and lack of commitment of the staff in charge of the area, insufficient supervision of compliance with the work entrusted and poor communication and cross-checking of information between the areas related to the control of the goods; This shows the inappropriate management of the company's inventories and the existence of irregularities that must be corrected in time to give the company the opportunity to recover and make the right decisions that will lead it to solvency and adequate profitability, typical of a competent and efficient company.
Ejecutar un Examen Especial de Auditoria conlleva mucho responsabilidad y entrega por parte del equipo de auditores y un compromiso infalible por parte de la empresa en toda su estructura organizacional. La auditoria es indispensable, ya que permite prevenir o enfrentar problemas y posibles patrones de riesgos significativos; sus etapas son muy explicitas que nos llevan a conocer desde la problemática real de la empresa hasta sus posibles soluciones. Aquí empleamos la metodología descriptiva-explicativa para la indagación eficiente y veraz que se respalda en los artículos científicos expuestos. Este caso planteado va dirigido a la revisión y análisis exhaustivo del proceso de control interno sobre los inventarios de mercaderías que lleva a cabo la empresa EXFRU S.A. en el periodo de junio del 2019. En base a técnicas y procedimientos aplicados durante el proceso de auditoria se ha logrado obtener información relevante y determinante para la empresa; como es la verificación del incumplimiento fatídico de las políticas existentes, la irresponsabilidad y falta de compromiso del personal a cargo del rubro; la insuficiente supervisión del cumplimiento del trabajo encomendado y la deficiente comunicación y cruce de información entre las áreas relacionadas al control de las mercaderías; lo cual evidencia el inapropiado manejo de los inventarios que realiza la empresa y la existencia de irregularidades que deben ser corregidos a tiempo para otorgar a la entidad la oportunidad de recuperación y toma de decisiones correctas que la llevarán a la solvencia y rentabilidad adecuada, propias de una empresa competente y eficaz.
Keywords: AUDITORIA; INVENTARIOS; CONTROL INTERNO